Evaluation and polimodal treatment of pain skeletic and abdominal muscle in equines. (Revista Sistemas de Producción Agroecológicos, 2020)
Pain is one of the most important aspects that suggest a welfare state in animals. Because we cannot directly access to emotional states in them, the assessment of well-being is based on physiological factors and behavioral indicators. Veterinarians rely on the interpretation of the behavior of their patients in order to guide the most appropriate medical treatment; however, the clinical evaluation of pain in animals is a subjective procedure dominated by personal bias, perception and physiology. In recent years, research has focused on the creation of pain scales (visual analogue scale, simple descriptive scale, numerical rating scale, time budget analysis, composite pain scale and grimace scales) in order to facilitate to the clinician the determination of the degree of pain experienced by the patient. Pharmacological approaches for the treatment of pain in horses should be based and selected for specific purposes (inflammation, nerve injury), (peripheral versus central sensitization), and depending on the severity and type of pain (somatic versus visceral; mild or severe), however most of the drugs used to treat pain in horses are divided into 4 broad categories: anti-inflammatory drugs (NSAIDs), steroids and non-steroids, opioids, and α2 agonists, despite the analgesic properties of These drugs, there are reports of various adverse effects associated with their use. The polymodal analgesia is an alternative, although it does not contemplate new pharmacological groups, it proposes the simultaneous use of several medications that by having different mechanisms of action, manage to improve the final analgesic effect, diminishing the risks of presentation of adverse effects.
Keywords: pain; pain scales; equine; polymodal analgesia